High‐resolution integrated calcareous plankton biostratigraphy and magnetostratigraphy at the Oligocene–Miocene transition in Southwestern Atlantic Ocean. (24th July 2017) - Gennari, Rocco; Persico, Davide; Turco, Elena; Villa, Giuliana; Iaccarino, Silvia Maria; Florindo, Fabio; Lurcock, Pontus C.; de Santana dos Anjos Zerfass, Geise
Abstract : After the formalization of the base of the Miocene in the Lemme‐Carrosio section (Italy) at the base of Subchron C6Cn.2n, the calcareous plankton biostratigraphy was refined in several open ocean Deep Sea Drilling Project/Ocean Drilling Program sites. However, high‐resolution quantitative biostratigraphic studies, integrating planktonic foraminifera and calcareous nannofossils, are still lacking for the time interval spanning the Oligocene–Miocene transition. Here, we present a reinvestigation of Deep Sea Drilling Project Hole 516F (Rio Grande Rise) and 4 oil wells drilled by Petróbras Brasileiro SA in the Campos Basin (SW Atlantic Ocean). We identified 12 planktonic foraminiferal and 18 calcareous nannofossil bioevents that have been integrated with an updated magnetostratigraphy of Hole 516F allowing the correlation with the GPTS and the identification of the Oligocene/Miocene boundary (base of Subchron C6Cn.2n) between the Top of Sphenolithus delphix and the Base of common Paragloborotalia kugleri . Furthermore, our results give new insights on the reliability of major calcareous plankton events across the Oligocene–Miocene transition: (a) the Sphenolithus ciperoensis Top, the S. delphix Base and Top, and the Sphenolithus cometa Base are reliable events at a global scale; (b) the Bases of Globoquadrina dehiscens and Sphenolithus disbelemnos  > 4 μm are correlatable events only within the study sector of the SW Atlantic Ocean; and (c) the Globoturborotalita ciperoensis Top, Globoturborotalita angulisuturalis Top, and Sphenolithus procerus Base are diachronous. Finally, previously unreported biostratigraphic data, such as the distribution range of S. disbelemnos  < 4 μm and Sphenolithus cf. S. pseudoheteromorphus, the Tenuitellinata praestainforthi acme interval, and the Top of common Globigerinoides primordius were identified in the Campos Basin.